Bydgoszcz - pasja życia. Edmund Czajkowski (1921-2012) (Kronika Bydgoska, 2012)
Bydgoszcz - the passion of life. Edmund Czajkowski (1921-2012)’. A remembrance of a resident of Bydgoszcz, power engineer and famous social activist. Edmund Czajkowski worked at the Pomeranian District Power Plant and later at the Power Generation Plant. In the years 1945-1976, he was a draftsman, construction manager, and supervision inspector of, among others, 60, 110 and 220 kV lines in Pomerania and Wielkopolska. He was known as a meritorious activist of the Friends of Bydgoszcz Association, enthusiast of collecting photographs and documents of old Bydgoszcz, author of numerous publications about the city’s history, and co-author of the monumental ‘An outline history of the Bydgoszcz Power Generation Plant’ published on the centennial anniversary of the company’s existence.